Selaginella chuweimingii (Selaginellaceae) sp. nov. from Yunnan, China - Zhou, Xin-Mao; He, Zhao-Rong; Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2015)
A new lycophyte species, Selaginella chuweimingii, from central Yunnan, China is described and illustrated. Selaginella chuweimingii is similar to S. sinensis in the habit and the morphology of strobili and sporophylls, but the new species can easily be distinguished from the latter by having ovate or oblong-ovate ventral leaves, extremely asymmetrically dorsal leaves, and oblong-ovate to ovate-lanceolate axillary leaves. Also the new species has lamellate ornamentation on megaspore surfaces and less prominent verrucae and ridges on microspore surfaces. The two species are further separated in geographical distribution with the new species occurring in central Yunnan Province while S. sinensis in northern and eastern China.